Contributive Effect of Land Management Indicators to Farmers Farmland Conservation in Oyo State, Nigeria - Oyewo, I. O.; Adeoye, A. S.; Adesope, A. A.; Adisa, A. S.; Oke, O. S.; Farayola, C. O.; Elesho, R. O.; Aluko, A. K. (NIU Journal of Social Sciences; Vol 9 No 3 (2023): NIU Journal of Social Sciences, Vol. 9 No. 3, September 2023, 2023)
Major problem facing tropical agriculture is the inherent low fertility status of most of the soils because of the predominant low-activity. The study explained the contributive effect of sustainable land management indicators to land use on farmers’ productivity in Oyo State Nigeria. A two-stage sampling technique was employed in selecting 330 farmers from the four agricultural zones in Oyo State. Structured questionnaire was used to obtain primary data. The data collected were analysed using descriptive and Fuzzy logic analysis (Fuzzy set theory). The result revealed that the result of Fuzzy Logic which was used to compute the composite indicators of unsustainable land use (IULU) showed that the total IULU of 0.26 obtained indicated that farmers’ land management practices in the study area are generally sustainable. Residue cover, land fallowing, compaction and rooting, salinity and crop rotations among others have the highest relative contributions of 3.2%, 3.2%, 3.2%, 3.2% and 3.2% respectively to land farmers land conservation, while other indicators contribute lower percentage to land conservation been unsustainable in the study with relative contributions of 2.1%, 2.3%, 2.3%, 2.0, 2.5% and 2.4% respectively also majority of the farmer (60%) are sustainable and contributed larger percentage (96.4%) to sustainability and had between 0.1-0.2 with minimum of 0.00004 and maximum of 0.95650 sustainable land index in the study. The study recommended among others that cultural practices for erosion prevention should be encouraged by planting of cover crops and planting of trees and other agronomic best practices which enhance soil conservation and improve more on their level of sustainable land use indicators.     Keywords: Sustainable, Land, Conservation, Indicators, Aggregation, Fuzzy, Nigeria